Vilka kvalitetsfaktorer anses viktigast vid inköp av grönsaker och frukt för återförsäljare i Sverige - Carrwik, Charlotte (2008)
Since Sweden joined the European Union all Swedish fruit and vegetables are classified according to EU Quality standards. One important function is the product description and how it can facilitate the trade; for example in better comparing prices and also to guarantee the quality of the product. This quality standards or product descriptions are written as words of an Act and obligatory for all countries that has joined the EU. It's often a demand from the customers to be certificated according to some of many certificating systems. One example is the common worldwide GLOBAL GAP-certification system created by the organisation EUREP which represents the leading European retail traders. The purpose of this thesis is to identify and list the five most important factors for purchase of vegetables and fruit in wholesale trade. The result, the most determining factors, can facilitate and promote better understanding and co-operation in the chain of sales and distribution. Which factors of quality do purchasers consider are the most important and why? Interview with five purchasers at some of the largest wholesale dealers in Sweden has been carried out. The interviews resulted in rather uniform answers; the key factors the purchasers mention was approximate in the same area. It is also obvious that the word "quality" is much more than just the "quality" of the product. Its also include factors like for example; cultivation, the impact of the environment, transports and the labour conditions. The results showed a list of five key purchasing factors: 1) the quality of product, 2) price, 3) food safety, 4) guarantee of supply and 5) innovation. These factors are to a large extent, also a result of laws and rules for vegetables and fruit for members in the EU. For example the rules of quality in EU and they are not voluntarily. Different types of certifications can in theory be voluntarily, but they are in practice, often a condition for trade and a key demand from the costumers. Guarantee of supply and innovation, for example keenly alive to and understanding for the wholesale dealers and their costumers, are often conditions for competition. The suppliers should also know the market well and understand the importance of product development.One main characteristic of this fruit and vegetables business from the wholesale point of view, are focus on giving high value to the end customer and that all the participants (in the chain of distribution) together improve the overall business.